LITERATUR REVIEW: PENGEMBANGAN MODEL GREEN HUMAN RESOURCE MANAGEMENT UNTUK MENDUKUNG KEBERLANJUTAN WISATA SUNGAI DI BANJARMASIN: - Bunga Villia ira; Lindari Lindari; Firdanita Wandira Dwi Putri; Debi Septiani; Irfan Naufal Zhulyadaini (Majalah Ilmiah Manajemen STIE Aprin Palembang, 2024)
This article aims to develop a conceptual model of Green Human Resource Management (GHRM) to support the sustainability of river-based tourism in Banjarmasin through a literature review approach. The study synthesizes recent research on GHRM practices in the tourism and hospitality sectors, including green recruitment and selection, green training, green performance management, green rewards, and employee green involvement, and relates them to the context of river tourism sustainability. The literature shows that GHRM can enhance employees’ green abilities, motivation, and opportunities, which in turn strengthen environmental performance, operational efficiency, and the attractiveness of sustainable tourism destinations. In the specific context of Banjarmasin, which is known for its river-based tourism yet faces environmental and management challenges,GHRMis positionedas a strategicleverto build a green organizationalculture, encouragepro‑environmentalbehavior,andsupportgreeninnovationintourismservices.This articleproposesa GHRM-based model that linksgreen HR practiceswith key outcomes such as employee sustainable performance and sustainable tourism organization performance, providing a conceptual foundation for future empirical research and practical initiativesin Banjarmasin’s river tourism sector.